Levels of inference in reading comprehension - Abduramanova , Nezire (The Lingua Spectrum, 2025)
This article provides a thorough exploration of inferencing as a critical skill in reading comprehension, particularly emphasizing its necessity for English as a Foreign Language (EFL) learners. It begins by defining inferencing as the ability to synthesize textual clues with prior knowledge to grasp unstated meanings, positioning it as foundational for deep comprehension. The author delineates the intricate relationship between lower-level reading processes (such as word recognition, orthographic, phonological, and semantic processing) and higher-level comprehension models (text and situation models), explaining how their automaticity and integration are crucial for fluent reading and nuanced understanding. A significant portion of the article is dedicated to lexical inferencing, defining it and outlining the various knowledge sources (grammatical, morphological, L1, world, and discourse knowledge) L2 readers employ. Crucially, the article offers practical, research-backed strategies for developing lexical inferencing skills in L2 contexts, including the importance of comprehensible input, thematic reading, verification, explicit instruction on cue types, and consistent practice. Ultimately, the piece argues that mastering inferencing transforms readers from passive decoders into active, insightful interpreters, equipping EFL learners with the critical thinking and communicative competence vital for academic success and real-world interactions.